2005
DOI: 10.1016/j.femsyr.2005.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Pectinolytic enzymes secreted by yeasts from tropical fruits

Abstract: Three hundred yeasts isolated from tropical fruits were screened in relation to secretion of pectinases. Twenty-one isolates were able to produce polygalacturonase and among them seven isolates could secrete pectin lyase. None of the isolates was able to secrete pectin methylesterase. The pectinolytic yeasts identified belonged to six different genera. Kluyveromyces wickerhamii isolated from the fruit mangaba (Hancornia speciosa) secreted the highest amount of polygalacturonase, followed by K. marxianus and St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
10

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 43 publications
5
41
0
10
Order By: Relevance
“…The Petri dishes were incubated at 30 °C for 3 days and then flooded with 5 N HCl. Pectinolytic activity was indicated by the formation of a clear halo around the colonies (SCHWAN; COOPER; WHEALS, 1997;DA SILVA et al, 2005).…”
Section: Screening Of Yeasts For Pectinase Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Petri dishes were incubated at 30 °C for 3 days and then flooded with 5 N HCl. Pectinolytic activity was indicated by the formation of a clear halo around the colonies (SCHWAN; COOPER; WHEALS, 1997;DA SILVA et al, 2005).…”
Section: Screening Of Yeasts For Pectinase Productionmentioning
confidence: 99%
“…As far as it is known; these enzymes could be involved in substrate colonization (fruits). This causes the breakdown of plant tissues with the concomitant release of sugars from plant cells, which in turn can be used for yeast growth, hence causing further spoilage (DA SILVA et al, 2005). It can be concluded that W. anomalus may belong to the second group of yeasts.…”
Section: Sequencing Of Its1-58s-its4 Amplicon Allowed Confirming Thementioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented, that several organisms are able to produce pectin degrading enzymes including plants, filamentous fungi, bacteria and yeast [9][10][11][12]. For industrial purposes moulds such as Aspergillus niger, Coniotryrium diplodiela, Penicillum and Rhizopus species are preferred, because as much as 90% of the enzyme can be excreted into the culture medium [9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For industrial purposes moulds such as Aspergillus niger, Coniotryrium diplodiela, Penicillum and Rhizopus species are preferred, because as much as 90% of the enzyme can be excreted into the culture medium [9,[13][14][15]. Pectinase production by filamentous fungi varies according to the type of strain, cultivation conditions (pH, temperature, aeration, agitation and incubation time) and the growth medium composition (particularly carbon and nitrogen sources) [16].…”
Section: Introductionmentioning
confidence: 99%